Savannah Reid : And the Killer Is... - Book 25 - McKevett, G. A (New York, NY : Kensington Books, 2020)
When a 90-year-old former movie star is murdered inside her derelict 1920s mansion, plus-sized PI Savannah Reid, Dirk, and the Moonlight Magnolia gang search for her killer by exploring the "good old days" of Hollywood-when both she and Tinsel Town were young, but far from innocent.
Keywords: Reid, Savannah (Fictitious character) -- Fiction; Women private investigators -- Fiction; Murder -- Investigation; Fiction; Overweight women -- Fiction; Older women -- Crimes against; Fiction; Actresses -- Crimes against; Fiction; California, Southern -- Fiction; Hollywood (Los Angeles, Calif.) -- Fiction; Detective and mystery fiction